Enxergando a acuidade visual e sua relação com o desempenho de escolares de um município do interior da Bahia - Matos, Antonio Luis Gomes de (2025)
Visual acuity (VA) is a critical factor in the learning process, yet it is often overlooked in school environments. This study aimed to investigate the relationship between low visual acuity (LVA) and academic performance among adolescents attending a public high school in Feira de Santana, Bahia, Brazil. A quantitative, cross-sectional study was conducted in 2024, involving 251 students aged 14–19 years. Data collection included visual screening with the Snellen chart, administration of a sociodemographic questionnaire, and assessment of the School Performance Coefficient (SPC). The prevalence of LVA was 48.2%, with statistically significant associations observed with family income (p = 0.019), absence of ophthalmologic consultations (p < 0.05), irregular or absent use of corrective lenses (p < 0.05), and lower overall academic performance (p = 0.012), particularly in Humanities subjects (p = 0.006). The findings indicate that visual impairment is an important risk factor for poor school performance and underscore the need for intersectoral public policies aimed at visual screening and eye health promotion within the school setting. Strengthening collaboration between health and education sectors is essential to promote equitable learning opportunities and educational development for adolescents in socially vulnerable contexts.